2006
DOI: 10.1111/j.1365-3024.2006.00906.x
|View full text |Cite
|
Sign up to set email alerts
|

Gonadectomy and progesterone treatment induce protection in murine cysticercosis

Abstract: The effects of progesterone on castrated mice of both sexes infected with Taenia crassiceps cysticerci were studied. Gonadectomy and treatment with progesterone before infection decreased parasite loads by 100% compared with intact uninfected mice. mRNA levels of IFN-gamma and IL-2 (typically associated to Th1-like profiles) were markedly decreased in infected gonadectomized (Gx) mice, whereas progesterone treatment of infected Gx mice did not affected its expression. mRNA levels of IL-4, and IL-10 (typically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 25 publications
(33 reference statements)
1
22
0
Order By: Relevance
“…For example, establishment, growth and reproduction of the cestode Taenia crassiceps in intact laboratory mice increased after progesterone treatment (Vargas-Villavicencio et al, 2005). In contrast, parasite loads decreased substantially in castrated mice treated with progesterone (Vargas-Villavicencio et al, 2006). Furthermore, pregnant laboratory hamsters infected with Leishmania panamensis demonstrated a lower parasite burden than non-pregnant control animals (Osorio et al, 2008) because their innate immunity was heightened via hormone-modulated (pregnancy-associated 17-β oestradiol and a progesterone metabolite pregnane) nitric oxide production (see also Sacks et al, 1999).…”
mentioning
confidence: 99%
“…For example, establishment, growth and reproduction of the cestode Taenia crassiceps in intact laboratory mice increased after progesterone treatment (Vargas-Villavicencio et al, 2005). In contrast, parasite loads decreased substantially in castrated mice treated with progesterone (Vargas-Villavicencio et al, 2006). Furthermore, pregnant laboratory hamsters infected with Leishmania panamensis demonstrated a lower parasite burden than non-pregnant control animals (Osorio et al, 2008) because their innate immunity was heightened via hormone-modulated (pregnancy-associated 17-β oestradiol and a progesterone metabolite pregnane) nitric oxide production (see also Sacks et al, 1999).…”
mentioning
confidence: 99%
“…In a second analysis, it was demonstrated that infected mice that received P4 treatment increased estrogen levels two-fold compared to infected control mice. (Vargas-Villavicencio et al, 2005;Vargas-Villavicencio et al, 2006). A flow chart of the main immunoendocrinological effects of T. crassiceps infection in male and female mice is depicted in Figure 1.…”
Section: Immuno-endocrine Interactions In the Hostmentioning
confidence: 99%
“…Even more, castrated mice of both genders treated with progesterone before infection, decreased parasite loads by 100% compared with intact uninfected mice. However the negative effects in the establishment, growth and reproduction of T. crassiceps was mediated by the metabolism of progesterone to DHEA in the adrenal gland of castrated animals (Vargas-Villavicencio et al, 2006). To strength out the notion of DHEA as a protective agent, we designed experiments to test this hypothesis, by incubating in vitro T. crassiceps cysticerci with increasing concentrations of DHEA, and by in vivo treating male and female mice with DHEA and infecting them with T. crassiceps cysticerci.…”
Section: Therapeutic Applications Of Hormones In Cysticercosis/taeniosismentioning
confidence: 99%
“…P 4 treatment has a dichotomic effect: if mice of both sexes are non-gonadectomized (intact), P 4 treatment increased parasite loads, possibly through manipulation of the specific cellular immune response, besides the steroid's promotion of parasite reproduction (Vargas-Villavicencio et al, 2005). However, if mice are gonadectomized, P 4 completely decreases parasite loads, an impressive and unprecedented cysticidal effect, the likes of which are absent from other preventive or therapeutic measures (Vargas-Villavicencio et al, 2006). These two experiments suggests that, in intact hosts, progesterone is metabolized to estradiol, that is permissive for parasite reproduction, while in castrated animals, there is an active metabolism of progesterone in the adrenal glands to androgens, resulting in a toxic effect in the parasite growth (VargasVillavicencio et al, 2005(VargasVillavicencio et al, , 2006.…”
Section: Immuno-endocrine Interactions In the Hostmentioning
confidence: 99%
“…More recently the ability of sex steroids to affect the immunological response directed against pathogenic agents, and importantly the direct effect of these molecules on these organisms, have gained attention. These effects are clearly evident during various parasitic diseases including malaria, schistosomiasis, toxoplasmosis, cysticercosis, trypanosomiasis and leishmaniasis, where strong steroid hormone regulation of the immune response, has been described (Remoué et al, 2001;do Prado et al, 1998;Satoskar & Alexander, 1995;Vargas-Villavicencio et al, 2006;Libonati et al, 2006;Liesenfield et al, 2001). For instance, sex steroids play a significant role in regulating the parasite load in experimental intraperitoneal Taenia crassiceps cysticercosis of male and female Balbc/anN mice.…”
Section: Introductionmentioning
confidence: 99%